Représentations symboliques et imaginaires de la femme dans l’oeuvre de Djamel Allam - Kahina KACI OUALI; Zakia DAID (Ussnan)
“Any cultural manifestation can be seen as a communication process” and song is part of it, because it reproduces the ideology, politics and culture of a given society. Kabyle song (or sung poetry) has been considered from the very beginning as a reflection of Amazigh (Kabyle) society, because “it is the type of expression best placed to evoke, inform, inform and better retranslate collective sensitivity.” The singer who conveys these poems has the status of “aḥeddad n wawal” (the blacksmith of speech and language), the holder of virtuous knowledge, of a neat and clean language like a young man who was able to having access to “taqbaylit” or the genius of speech which gives him the right to express himself in “tajmaεt” (the traditional djamaa). The Kabyle singer has always known how to reproduce the collective (common) memory, the opinion and the culture of his society. Djamel Allam is one of those who brought together modernity and tradition.